Analysis of Job Demands for Private University Lecturers - A. Nur Asri Ainun (Indonesian Journal of Innovation Multidisipliner Research, 2024)
Lecturer performance must be optimized in an effort to improve the quality of higher education. The aim of this research is to evaluate the job needs of lecturers at private universities in Makassar City. In this situation, work demands include various elements, such as work overload, time pressure, and clarity of tasks assigned (Role Ambiguity). Quantitative methods were used in this research. Questionnaires were distributed to lecturers at various private universities in Makassar City. The data collected was analyzed using the SPSS version 26 analysis program. The research results showed that what had a significant influence on lecturer performance was role ambiguity. Workoverload and time pressure have a positive but not significant effect. In addition, this research found that lecturers with more experience tend to be better at managing job demands compared to teachers with less experience.